Karakteristik Karakteristik Fisikokimia Papain Soluble Collagen dari Gelembung Renang Ikan Tuna (Thunnus sp.): Physicochemical Characteristics of Papain Soluble Collagen from Tuna (Thunnus sp.) Swim Bladder - Hari Cahyono; Wini Trilaksani; Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2022)
Collagen is a connective tissue protein composed of the amino acids glycine, proline, alanine and hydroxyproline, which are found in the skin, bones, scales and swim bladder tissue of fish. Fish swim bladder as a by-product of the fishing industry have the potential to be converted into halal collagen. This study aims to evaluate the effectiveness of the pre-extraction process of the combination of NaOH and ultrasonication and the use of papain enzyme in the extraction process on the physicochemical characteristics of tuna swim bladder collagen. The research method was a combination of pre-extraction of NaOH and 150 minutes of ultrasonication and immersion for 2; 4; 6; 8; 10; 12; 14; 16; 18; 20; 22 and 24 hours, extraction using the papain enzyme with a concentration of 0; 3,500 and 5,000 U/g and extraction time of 36 and 48 hours. The results showed that the pre-extraction process using 150 minutes of ultrasonication with soaking for 22 hours was the best time to eliminate non-collagen proteins, and extraction using papain enzyme with a concentration of 5,000 U/g and soaking for 36 hours was the preferred treatment for the degree of collagen development. The yield of collagen obtained was 7.01±0.4%, the dominant amino acids were glycine, arginine and proline, tuna swim bladder collagen had a protein band of α1 chain of 117 kDa, α2 chain of 107 kDa and β chain of 244 kDa and zeta potential value of 0.496 mV.